Simulation of Ice Growth in Process of Liquor Evaporation-Freezing by Fractal Theory - Penghui, Gao; Xingye, Zhou; Donghai, Zhang; Yijiang, Wang (Journal of Technology Innovations in Renewable Energy, 2014)
Considering complexity in process of the liquor’s evaporation-freezing and irregularity on the liquor surface, generating and developing model of ice on liquor surface was proposed by humidity difference based on fractal theory and diffusion limited aggregation model (DLA). The effect of gas flow velocity and humidity difference between gas and liquor surface on generating and developing of ice above liquor surface were analyzed by numerical simulation. The results showed that the fractal method could simulate the process generating and developing model of ice above liquor surface. It provided the new idea and method for the study of the liquor evaporation-freezing and ice growth.